Antioxidant effect of nigella oil on heated camel and rabbit meat - Kh. Rachchad; M. Farh; M. E. Khasmi (Теория и практика переработки мяса)
The exposure of meat to heating (cooking) or cold storage could alter its chemical composition. In this work, the oxidizing effect of heating on rabbit and camel meat, and the protective effect of nigella oil (NO) were evaluated and compared. Samples of rabbit and camel meat were treated with increasing doses of NO, and then were heated until reaching an internal temperature of 80 °C. Water loss, thiobarbituric acid reactive substances (TBARS) and carbonyls levels, as well as activities of catalase (CAT), glutathione peroxidase (GSHPx) and superoxide dismutase (SOD), were analyzed at different meat storage times. The results showed that heating of camel and rabbit meat induced a significant increase in the water loss, and TBARS and carbonyls levels, associated with a significant decrease in the activities of CAT, GSHPx and SOD. In both species, TBARS and carbonyls in the meat samples treated with NO before heating were significantly (P < 0.05) lower than those in the untreated samples, and decreased more and more when the NO dose increased. In the samples treated with NO, all enzymatic activities were significantly (P < 0.05) higher than those observed in the untreated samples, and increased more and more with increasing NO dose. The findings reveal a potential antioxidant power of NO preserving the organoleptic composition of heated camel and rabbit meat.